Observation of time-reversal symmetry breaking in the band structure of altermagnetic RuO2 - Fedchenko, Olena; Minár, Jan; Akashdeep, Akashdeep; D'Souza, Sunil Wilfred; Vasilyev, Dmitry; Tkach, Olena; Odenbreit, Lukas; Nguyen, Quynh; Kutnyakhov, Dmytro; Wind, Nils; Wenthaus, Lukas; Scholz, Markus; et al. (Science advances, 2024)
Altermagnets are an emerging elementary class of collinear magnets. Unlike ferromagnets, their distinct crystal symmetries inhibit magnetization while, unlike antiferromagnets, they promote strong spin polarization in the band structure. The corresponding unconventional mechanism of time-reversal symmetry breaking without magnetization in the electronic spectra has been regarded as a primary signature of altermagnetism but has not been experimentally visualized to date. We directly observe strong time-reversal symmetry breaking in the band structure of altermagnetic RuO2 by detecting magnetic circular dichroism in angle-resolved photoemission spectra. Our experimental results, supported by ab initio calculations, establish the microscopic electronic structure basis for a family of interesting phenomena and functionalities in fields ranging from topological matter to spintronics, which are based on the unconventional time-reversal symmetry breaking in altermagnets.